Desenvolvimento in vitro e criopreservação de sementes de orquídeas - Souza, Gilberto Rostirolla Batista de [UNESP] (2015)
Orchids are well appreciated by ornamental, ecological and economic potential. The improvement of genetic resources conservation methods through seeds and protocorms cryopreservation is an important strategy for the conservation of germplasm and plant breeding programs of this family. The domain of techniques for domestication and mass propagation of species is very important because, enables decreasing predation and reduce the cost of production of plants. The in vitro culture is a technique that allows the production of a large numbers of plants; however, there are many losses during the acclimatization period (ex vitro). This work aimed to evaluate different protocols for cryopreservation of Ionopsis utricularioides seeds, as well as the in vitro development of seedlings in alternative culture media and different environments of the orchids, Amblostoma amblostomoides and Cattleya percivaliana. In experiments on cryopreservation of seeds for each species, the experimental design was completely randomized with eight treatments and four replications each. The treatments were: T1) seeds without cryopreservation (control 1); T2) seeds cryopreserved without cryoprotectants (Control 2); T3) glycerol + PVS2; T4) glycerol + PVS2 + phloroglucinol; T5) sucrose + PVS2; T6) sucrose + PVS2 + phloroglucinol; T7) glycerol + sucrose + PVS2; and T8) + sucrose + glycerol + PVS2 + phloroglucinol and 10 repetitions. The variables analyzed were germination percentage, number of seedlings and protocorms and development of the seedlings formed. In the experiments on in vitro development of seedlings in an alternative culture media and in different environments, the experimental design was completely randomized for each species. There were six treatments [T1: MS medium (Murashige e Skoog) - under laboratory conditions; T2: ACM (Alternative Culture Medium) - under laboratory conditions; T3: MCA - black net with 50% shading; T4: MCA - black net with ...